2022
DOI: 10.1182/blood.2019004316
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic aldehydes in the hematopoietic system

Abstract: DNA damage threatens the integrity of hematopoietic stem cells (HSCs) and the production of blood. Over the last 10 years, a wealth of genetic and functional research has shown that simple reactive aldehydes such as formaldehyde are potent genotoxins to HSCs. Mammals have evolved a two-tier protection mechanism against aldehydes, consisting of aldehyde detoxification enzymes (tier one), and the Fanconi Anemia (FA) DNA repair pathway (tier two) to process any aldehyde-induced DNA damage. Loss of either tier of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 111 publications
1
20
0
Order By: Relevance
“…What is not controversial is a clear and emerging consensus that multiple genetic factors can influence the penetrance of the FA phenotype. The most compelling of these are studies from Patel and colleagues demonstrating that deficits in ethanol metabolism robustly induce a classic FA phenotype in FA deficient mice [ 59 , 60 , 61 , 62 , 63 ]. There are additional cellular changes that have the capacity to impact development of the FA phenotype, for example dysregulated TGF-β signaling [ 64 ] and MAD2 defects [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…What is not controversial is a clear and emerging consensus that multiple genetic factors can influence the penetrance of the FA phenotype. The most compelling of these are studies from Patel and colleagues demonstrating that deficits in ethanol metabolism robustly induce a classic FA phenotype in FA deficient mice [ 59 , 60 , 61 , 62 , 63 ]. There are additional cellular changes that have the capacity to impact development of the FA phenotype, for example dysregulated TGF-β signaling [ 64 ] and MAD2 defects [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fanconi anemia is a rare disease caused by mutations in DNA repair genes and characterized by bone marrow failure, developmental abnormalities and multiple cancer predisposition ( Auerbach, 2009 ; Kee and D'Andrea, 2012 ). Evidence has shown that naturally occurring and endogenous genotoxic aldehydes, such as formaldehyde and acetaldehyde, could be primary sources of DNA damage that induce genome instability in hemopoietic stem cells in Fanconi anemia patients ( Wang et al, 2022 ; Garaycoechea and Patel, 2014 ; Brooks and Zakhari, 2014 ). Hira et al showed that ALDH2 deficiency accelerated bone marrow failure in pediatric patients with Fanconi anemia ( Hira et al, 2013 ).…”
Section: Aldh2 Metabolism and Disease Beyond Alcoholmentioning
confidence: 99%
“…Recent studies in genetically modified mouse models combining deficiency of the aldehyde detoxification system and the FA pathway deficiency point to acetaldehyde and formaldehyde as important endogenous aldehydes that create ICLs [11][12][13] . Detoxifying enzymesacetaldehyde dehydrogenase 2 (ALDH2) and alcohol dehydrogenase 5 (ADH5)are required to metabolize these reactive aldehydes and prevent stem cell failure and leukemia in FA 14 . These findings are corroborated by human studies showing that dominant-negative ALDH2*2 variants in FA patients 15 and combined ADH5/ALDH2 deficiency both result in accelerated bone marrow failure and leukemia [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%